2017
DOI: 10.1038/srep45275
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-like oxidized low-density lipoprotein receptor-1 facilitates metastasis of gastric cancer through driving epithelial-mesenchymal transition and PI3K/Akt/GSK3β activation

Abstract: Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is a pattern recognition receptor that plays a critical role in vascular diseases and host immune response. Recently, our research discovered that LOX-1 could facilitate the uptake of dying cells and cross-presentation of cellular antigen via binding with heat shock proteins, which have a close relationship with gastric neoplasia. Therefore, we speculated that LOX-1 may serve as an oncogene in gastric cancer (GC) development and progression. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 47 publications
(53 reference statements)
1
24
0
Order By: Relevance
“…Each year, about 700,000 deaths were caused by GC, alarming the world of its diagnosis and treatment (Ferlay et al, ). Previous studies have certified that PI3K is an oncogene and P53 is a tumor suppressor gene in GC (Du, Liu, Wang, & Wang, ; Li et al, ). The present study showed that curcumin, a natural phytochemical, could inhibit PI3K pathway and activate P53 pathway in GC cells, thereby inducing apoptosis and autophagy.…”
Section: Discussionmentioning
confidence: 96%
“…Each year, about 700,000 deaths were caused by GC, alarming the world of its diagnosis and treatment (Ferlay et al, ). Previous studies have certified that PI3K is an oncogene and P53 is a tumor suppressor gene in GC (Du, Liu, Wang, & Wang, ; Li et al, ). The present study showed that curcumin, a natural phytochemical, could inhibit PI3K pathway and activate P53 pathway in GC cells, thereby inducing apoptosis and autophagy.…”
Section: Discussionmentioning
confidence: 96%
“…Metastasis is a high potential risk and the predominant cause of recurrence and mortality among patients with GC, and a number of cell biological activities are controlled in this multistep process, including adhesion, migration, invasion and angiogenesis (1). Lectin-like oxidized low-density lipoprotein receptor-1 was overexpressed in GC cells and increased the migratory and invasive ability by enhancing EMT, and activating the PI3K/Akt/glycogen synthase kinase 3β (GSK3β) pathway (53). Vascular endothelial growth factor-A (VEGF-A) was suggested to promote angiogenesis by activating the downstream Akt/mTOR cascade in GC (24).…”
Section: Direct Sequencingmentioning
confidence: 99%
“…In line with these findings, targeting influenza histocompatibility antigen-1 to LOX-1 elicits antigen-specific protective antibody response to virus in macaques suggesting a good candidate for vaccine development ( 39 ). Besides, several studies have reported a high expression of LOX-1 in various tumors including gastric ( 40 ), colorectal ( 41 ), and prostate ( 42 ) cancers, which correlates with a poor prognosis in patients ( 40 ). Functionally, LOX-1 was shown to promote tumor angiogenesis ( 42 ), metastasis ( 43 ), and the migration and invasion of gastric cancer cells by notably driving epithelial–mesenchymal transition ( 40 ).…”
Section: “(Dectin-1)” Familymentioning
confidence: 99%
“…Besides, several studies have reported a high expression of LOX-1 in various tumors including gastric ( 40 ), colorectal ( 41 ), and prostate ( 42 ) cancers, which correlates with a poor prognosis in patients ( 40 ). Functionally, LOX-1 was shown to promote tumor angiogenesis ( 42 ), metastasis ( 43 ), and the migration and invasion of gastric cancer cells by notably driving epithelial–mesenchymal transition ( 40 ). Interestingly, LOX-1 was recently identified to be particularly expressed by potent polymorphonuclear myeloid-derived suppressor cells from blood and tumor of patients with non-small cell lung or head neck cancer and to be associated with worse survival ( 44 ).…”
Section: “(Dectin-1)” Familymentioning
confidence: 99%